Moral Distress, Health and Intention to Leave: Critical Care Nurses' Perceptions During COVID-19 Pandemic - Maria Andersson PhD, CCN, RN; Angelica Fredholm Med Dr, RN; Anna Nordin PhD, CCN, RN; Åsa Engström PhD, CCN, RN (SAGE Publishing, 2023)
Introduction Moral distress increases the risk that critical care nurses will lose the ability to provide quality nursing care. Aims To describe person-related conditions and perceptions of moral distress, health and intention to leave among critical care nurses in intensive care units, and to examine the relationship between person-related conditions, moral distress, health and intention to leave. Method Cross-sectional, with 220 critical care nurses in 15 Swedish ICUs, and data gathered via a self-reported questionnaire. Results Highest moral distress scores were reported in futile care and poor teamwork and 21% reported entertaining an intention to leave. Self-reported health was lower than before the COVID-19 pandemic and 4.1% reported pronounced exhaustion disorder. Self-reported health, reduced capacity to tolerate demands under time pressure, emotional instability or irritability, physical weakness, or being more easily fatigued and with decreased well-being were factors that had a relationship with futile care. Sleeping problems and intention to leave had a relationship with poor teamwork. Conclusions Different strategies are needed to reduce moral distress and the leadership is crucial for managing crises such as the COVID-19 pandemic.